NASKAH AKADEMIK RANCANGAN PERATURAN DAERAH KABUPATEN PANGKAJENE DAN KEPULAUAN TENTANG PENCEGAHAN PERKAWINAN ANAK - Arifin, Arini; Mauliana, Deasy (ADMIT: Jurnal Administrasi Terapan, 2024)
Pangkajene and Kepulauan Regency has a relatively high intensity of child marriages and this influences community welfare. Child marriages in Pangkajene and Kepulauan Regency are caused by many factors, one of which is cultural factors, namely arranged marriages. Eliminating child marriage is one of the goals of Sustainable Development Goals (SDGs). Children have the right to receive protection from the state, government, parents, and society. in order to realize this, this research aims to prepare an academic paper of the academic draft of regional regulation of Pangkajene and Kepulauan regency on the prevention of child marriage as the argumentation basis in designing public policies regarding methods and strategies for preventing child marriage in Pangkajene and Kepulauan Regency. The preparation of this academic draft was carried out using data collection and analysis methods, namely qualitatively by conducting literature studies and literature studies as well as conducting interviews. The results of the research show that when compiling academic drafts, it is important to take law number 12 of 2011 into account. To prepare legal guidelines, researcher needs to pay attention to the effectiveness of these policies for people’s lives, both philosophically, sociologically and juridically. Apart from that, in preparing academic draft, regional regulation compositionneeds to include the scope, direction of regulation, and scope of the material they contain.